2011
DOI: 10.1017/s1751731110002296
|View full text |Cite
|
Sign up to set email alerts
|

Traceability of grass feeding in beef: terpenes, 2,3-octanedione and skatole accumulation in adipose tissue of young bulls

Abstract: The development of analytical methods to verify the production system of meat products requires the identification of biomarkers that can trace the product's origin, and secondly the factors that govern the deposition of these markers in animal tissue need to be defined. In this study, 2,3-octanedione, skatole and terpenes were selected as biomarkers, and their deposition was investigated in bull calves reared under three different strategies. All of the animals were reared indoors until approximately 150 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 23 publications
3
15
0
9
Order By: Relevance
“…Prache et al (2005) suggested that terpenoids could be used not only to recognize the type of diet animals consume but also to localize the geographical origin of pasturefed animals. Furthermore, Serrano et al (2011) reported that a higher accumulation of terpenoids was observed in perirenal and intraperitoneal fat compared to intermuscular and subcutaneous fat.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prache et al (2005) suggested that terpenoids could be used not only to recognize the type of diet animals consume but also to localize the geographical origin of pasturefed animals. Furthermore, Serrano et al (2011) reported that a higher accumulation of terpenoids was observed in perirenal and intraperitoneal fat compared to intermuscular and subcutaneous fat.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have managed to find compounds in beef that could be used as herbage feeding tracers, based on the significant effect of the feeding system on the volatile composition of beef (Prache et al, 2005;Serrano et al, 2011;Vasta et al, 2012). Higher levels in the volatile fraction of meat and fat of skatole, 2,3-octanodione and several terpenoids, especially sesquiterpenes, such as aromadendrene, γ-cadinene or germacrene D, among others, led to the conclusion that those compounds could be used as indicators of pasture diets in cattle (Vasta and Priolo, 2006;Serrano et al, 2011;Vasta et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts have been made to use the profiles of stable isotopes, fatty acids and other organic compounds in the meat and adipose tissue of animals (Serrano et al, 2011), DNA (Nicoloso et al, 2013), carotenoids and vitamin A in plasma; additionally, other biological fluids (Álvarez et al, 2015) could be used as discriminators of geographic origin, type of diet or production system of meat. Indirect authentication systems usually require slaughtering the animal to take samples, and to some degree, they are subject to adulteration in the results.…”
Section: Introductionmentioning
confidence: 99%
“…A number of specific compounds in the meat have been identified as biomarkers of pasture-feeding, such as carotenoid pigments (Prache and Thériez, 1999;Serrano et al, 2006;Alvarez et al, 2014), fatty acid composition (Aurousseau et al, 2004 and2007) and volatile compounds Serrano et al, 2011). Assay of these different components necessitates various analytical techniques, and the data often have to be further combined to overcome confounding factors and the possibility of fraud (Prache et al, 2009).…”
Section: Introductionmentioning
confidence: 99%